2019
DOI: 10.1590/1982-02592019v22n3p536
|View full text |Cite
|
Sign up to set email alerts
|

A Universidade pública em tempos de ajustes neoliberais e desmonte de direitos

Abstract: Resumo Neste estudo é apresentada uma análise da educação pública brasileira, com enfoque no ensino superior, que toma por base o histórico da contínua disputa entre projetos para área, considerando suas consequências para a educação brasileira ao longo do tempo. Ao mesmo tempo, busca-se expressar a perspectiva daqueles que estão comprometidos com a luta por uma alternativa transformadora e emancipatória para a educação, diante da conjuntura de ofensiva neoliberal e retirada de direitos. Através das categorias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 1 publication
1
16
0
10
Order By: Relevance
“…Thus, it is noted that, in these spaces, there is production of science and dissemination of new essential knowledge for society. 9,10 This reinforces the reason why the participants reported that being a specialist graduating from a public university is a driving factor for the insertion and maintenance of the stomatherapist in the world of work. Despite the difficulties that permeate public education in Brazil, there is still, in these places, great incentive to the production of science and the qualification of teachers, in addition to the constant concern with quality teaching, at the undergraduate and graduate levels.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Thus, it is noted that, in these spaces, there is production of science and dissemination of new essential knowledge for society. 9,10 This reinforces the reason why the participants reported that being a specialist graduating from a public university is a driving factor for the insertion and maintenance of the stomatherapist in the world of work. Despite the difficulties that permeate public education in Brazil, there is still, in these places, great incentive to the production of science and the qualification of teachers, in addition to the constant concern with quality teaching, at the undergraduate and graduate levels.…”
Section: Discussionsupporting
confidence: 58%
“…In the universities, it is possible to express opinions, attitudes and projects that contribute to produce knowledge and train/ qualify professionals. 9,10 Public universities have high standards of teaching and research, maintain a high degree of independence, with regard to the immediate determinations of the market, despite the external pressures they suffer to train human resources and develop research studies, according to the interest of capital, and not, imperiously, based on social needs. Thus, it is noted that, in these spaces, there is production of science and dissemination of new essential knowledge for society.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a daily life, when Brazilian subjects are forced to live with an unknown virus, while experiencing ineffective forms of pandemic management, what appearances would be populating the dreams of Brazilians? In the case of teachers and students, there is a recurring oneiric narrative that refers to the risk of extinction of federal public universities in the face of the astonishing setback in educational policies since 2016 15 .…”
Section: Dreams Politics and Pandemics -The (Extra)ordinary Experiencesmentioning
confidence: 99%
“…Como aponta Christian Laval (2019), embora não exista ensino sem ideais humanos, os anelos de uma formação para a cidadania e para a vida vêm sendo soterrados pelo imperativo de ajustar o sujeito ao mercado, em uma sociedade que tende para a extinção de inúmeras formas de atividade laborativa e desperdiça um enorme contingente de trabalhadores, mesmo entre os mais preparados academicamente. O ideal de ajustamento ao trabalho precarizado forma os estudantes abstratamente, propondo formas de atividade cada vez mais identificadas ao "empreendedorismo", ao individualismo e à busca de interesses egoístas em detrimento de ideais sociais mais amplos (LUSA et al, 2019).…”
Section: Psicologia E Direitos Humanos Na Formação: Da Práxis à Teoriaunclassified